Submodul Prima Lemah dan Submodul Hampir Prima Pada Z‐modul M_2x2 (Z_9) - Wardhana, I Gede Adhitya Wisnu; Switrayni, Ni Wayan; Aini, Qurratul (University of Mataram, 2018)
Prime submodule is the abstraction to module theory of prime ideal in ring theory. A proper submodule N of an R-module M is called prime submodule if for all r in R and m in M such that rm in N implies r in (N:M) or m in N. Prime submodule also generalized into weakly prime submodule and almost prime submodule. This study deal with particular cases of both of them in Z-module M_2x2(Z_9), the three submodules are equivalent in case of non-zero submodule.